2019
DOI: 10.1186/s13662-019-1965-z
|View full text |Cite
|
Sign up to set email alerts
|

Existence results in Banach space for a nonlinear impulsive system

Abstract: We deal with three important aspects of a generalized impulsive fractional order differential equation (DE) involving a nonlinear p-Laplacian operator: the existence of a solution, the uniqueness and the Hyers-Ulam stability. Our problem involves Caputo's fractional derivative. For these goals, we establish an equivalent fractional integral form of the problem and use a topological degree approach for the existence and uniqueness of the solution (EUS). Next, we check the stability of the suggested problem and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 24 publications
(29 reference statements)
0
17
0
Order By: Relevance
“…In this paper, we mainly consider a kind of ψ-Hilfer fractional order differential equation. The addressed equation has time-varying delay terms and non-instantaneous impulsive effects, which are quite different from the related references discussed in the literature [18,19,21,22,[38][39][40][41][42]. The nonlinear fractional order differential system studied in the present paper is more generalized and more practical.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…In this paper, we mainly consider a kind of ψ-Hilfer fractional order differential equation. The addressed equation has time-varying delay terms and non-instantaneous impulsive effects, which are quite different from the related references discussed in the literature [18,19,21,22,[38][39][40][41][42]. The nonlinear fractional order differential system studied in the present paper is more generalized and more practical.…”
Section: Resultsmentioning
confidence: 79%
“…In [20], Ameen et al studied the Ulam stability and existence theorems for Caputo generalized fractional differential equations where the kernel of the fractional derivative was function dependent so that the result generalized many existing results in history. Further, for more details about some other properties of the solutions, we can see [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…Fractional calculus based on differential and difference equations is of considerable importance due to their connection with real-world problems that depend not only on the instant time but also on the previous time, in particular, modeling the phenomena by means of fractals, random walk processes, control theory, signal processing, acoustics, and so on (see [1][2][3][4][5][6][7][8][9][10][11][12]). It has been shown that fractional-order models are much more adequate than integer-order models.…”
Section: Introduction and Prelimnariesmentioning
confidence: 99%
“…We suggest the readers for more detail about the fractional calculus and its application to the work in [1][2][3][4][5][6][7]. Among the fractional operators, the Caputo-Fabrizio [8][9][10] and the Atangana-Baleanu fractional differential operators with nonsingular kernel [4][5][6][7][11][12][13][14][15] are recently well studied operators.…”
Section: Introductionmentioning
confidence: 99%